Methods and reporting of studies assessing the impact of adherence to clinical practice guidelines: a scoping review - Batoul Yazbeck; Isabelle Boutron; Raphaël Porcher; Carolina Riveros; Philippe Ravaud; Sally Yaacoub (BMC Medicine)
Abstract Background Ensuring adherence to clinical practice guidelines (CPGs) is critical for improving patient outcomes. However, how the impact of guideline adherence on clinical outcomes is studied remains unclear. Our objectives are (1) to identify studies that assess the impact of adherence to CPGs; (2) to describe the research questions of these studies; and (3) to describe their study designs, methods, and reporting. We focused on CPGs addressing the pharmacologic management of major chronic diseases, specifically musculoskeletal diseases (rheumatoid arthritis, osteoarthritis, axial spondyloarthritis, and psoriatic arthritis), diabetes, and hypertension. Methods We conducted a scoping review. We searched PubMed on March 3, 2023, for studies published since 2013. We included studies assessing the impact of adherence to CPGs for the pharmacologic management of adult patients. One reviewer screened the titles and abstracts and full texts and a second reviewer independently screened 20%. Two reviewers independently extracted data using a standardized pilot-tested data extraction form. Data were analyzed descriptively. Results Of 7952 records retrieved, 16 studies were eligible for inclusion. The studies addressed CPGs for the management of diabetes (n = 8), hypertension (n = 6), and axial spondyloarthritis (n = 2). All studies were cohort studies, but none emulated a target trial. The median number of participants analyzed was 511 (IQR 350; 10,536) and the median follow-up time was 9 months (IQR 4; 18). Four studies explicitly reported the recommendations for which the impact of adherence was assessed, nine precisely defined adherence, and eight studies evaluated only surrogate outcomes. Thirteen studies accounted for confounding factors. There was serious or critical risk of bias in selection of participants in 13 studies. Conclusions The impact of adherence to clinical practice guidelines is rarely and inadequately evaluated. Future research should employ rigorous study designs and reporting standards to generate more reliable insights into the impact of CPG adherence.